Epidemiology and risk factors for varicella zoster virus reactivation in heart transplant recipients. Issue 3 (9th December 2020) - La Hoz, Ricardo M.; Wallace, Ashley; Barros, Nicolas; Xie, Donglu; Hynan, Linda S.; Liu, Terrence; Yek, Christina; Schexnayder, Scott; Grodin, Justin L.; Garg, Sonia; Drazner, Mark H.; Peltz, Matthias; et al.
Abstract: Heart transplant (HT) recipients are at higher risk of varicella zoster virus (VZV) reactivation. Risk factors for VZV reactivation are currently not well defined, impeding the ability to design and implement strategies to minimize the burden of this illness in this population. Automated data extraction tools were used to retrieve data from the electronic health record (EHR) of all adult HT recipients at our center between 2010 and 2016. Information from the Organ Procurement and Transplantation Network Standard Analysis and Research Files was merged with the extracted data. Potential cases were manually reviewed and adjudicated using consensus definitions. Cumulative incidence and risk factors for VZV reactivation in HT recipients were assessed by the Kaplan‐Meier method and Cox modeling, respectively. In 203 HT recipients, the cumulative incidence of VZV reactivation at 8‐years post‐transplantation was 26.4% (95% CI: 17.8‐38.0). The median time to VZV reactivation was 2.1 years (IQR, 1.5‐4.1). Half (14/28) of the cases experienced post‐herpetic neuralgia (PHN). Post‐transplant CMV infection (HR 9.05 [95% CI: 3.76‐21.77) and post‐transplant pulse‐dose steroids (HR 3.19 [95% CI: 1.05‐9.68]) were independently associated with a higher risk of VZV reactivation in multivariable modeling. Identification of risk factors will aid in the development of targeted preventive strategies.